ON DERIVATIVES ESTIMATION OF SMOOTHED DIGITAL CURVES - Glasa, Ján (Computing and Informatics, 2012)
In this paper new linear operators for the first derivatives estimation of smoothed digital curves are presented. They correspond to digital curves smoothing by various non-negative kernels.